Community in the Permanent Supportive Housing Model: Applications to Survivors of Intimate Partner Violence. Issue 4 (7th August 2020) - Hetling, Andrea; Dunford, Amy; Botein, Hilary
ABSTRACT: A key aspect of permanent supportive housing (PSH) is the community it forms, providing social supports and a sense of home for residents. Only recently, however, have evaluations of PSH examined community as an integral characteristic. For intimate partner violence (IPV) survivors, a new PSH target population, community and social connections are uniquely important. Using a case study of a PSH program for IPV survivors, we explored residents' experiences of a community. Based on feminist-grounded theory, we conducted in-depth interviews with 13 survivors over a two-year period. Findings indicate that some residents experience community in terms of shared physical space and shared identity and that positive interactions exist. However, the system of supports was fragile and inconsistent. We discuss strategies to strengthen community within PSH, but also argue for an expanded definition of community that reflects the diverse backgrounds and circumstances of residents.